Their hearts burned walking with Jesus along the Emmaus Road: an excursion through the Old Testament - O'Donnell, Kevin (Oxford, UK Monarch, 2006)
Includes bibliographical references.
Keywords: Bible. O.T. -- Introductions; Emmaus Road